فتاوى شيخ الإسلام ابن تيمية في المعاملات المالية وأثرها على المعاملات المالية المعاصرة دراسة وصفية تحليلية فقهية - Ruyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Ruyanto. Fatwas of Sheikh al-Islam Ibn Taymiyyah on financial transactions and their impact on contemporary financial transactions, a descriptive, analytical, jurisprudential study. Under the supervision of: Dr. Ibdal Syah and Dr. Hari Susanto. The subject of this letter revolves around the fatwas of a great scholar, Sheikh al-Islam Ibn Taymiyyah, in an important chapter, the chapter on financial transactions, with linking these fatwas to clarifying their impact on contemporary financial transactions from the perspective of Islamic jurisprudence. The importance of this message highlights the people’s need to know and understand the jurisprudence of financial transactions, as it is the backbone of people’s lives, and the focus of many of their needs. The street has taken into account that, making the original solution. And it enjoins what is necessary from it and forbids what is in it apparent or hidden corruption, and when there is an urgent need or a compelling necessity for a transaction and refraining from it results in greater harm than doing it, then the legislator then permits the act or omission, keeping the general legislation in order to preserve the public interest and to ensure the interest the individual without escaping. What is important in all this is to preserve the purposes of Sharia. The aim of this research is to highlight the impact of the fatwas of Sheikh Al-Islam Ibn Taymiyyah on financial transactions on contemporary financial transactions. The research relied on the inductive approach in its statement, the descriptive and analytical approach, and the method used by the researcher is to refer to the main sources. As for the type of research, it is desk research in that the research depends on books in collecting and analyzing its information. Among the most important conclusions reached by the research, including: Ibn Taymiyyah’s high-level scholarly position in his jurisprudential fatwas with a general view and finance in a particular view. Then the importance of knowing the chapter on financial transactions that have developed in it brilliantly and need its legal ruling and an attempt to extract provisions for these facts from the branches of jurisprudence, and one of its most important results is also that Ibn Taymiyyah’s fatwas on financial transactions greatly affect the various contemporary financial transactions. In particular, his fatwas infer It has and affects the fatwas of the National Shariah Board of the Indonesian Ulema Council. (Fatwa DSN MUI).